2022
DOI: 10.55927/eajmr.v1i5.488
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Good Corporate Governance on Banking Profitability

Abstract: This study aims to determine and analyze the effect of Good Corporate Governance on profitability in the banking sector listed on the Indonesia Stock Exchange. Proxies of good corporate governance are managerial ownership, institutional ownership, the composition of independent commissioners, and the size of the board of directors, profitability is proxied by the ratio of Return on Net Operating Assets (RNOA). The sample of this research was taken using purposive sampling to obtain 43 companies that meet the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous research conducted by (Karamoy & Tulung, 2020) found that corporate governance and financial performance have no effect on stock prices. According to (Pendong et al, 2022), good corporate governance can be interpreted as a structure and system that regulate the relationship between management (agents) and shareholders (principals). So there needs to be attention paid to company performance and the implementation of good corporate governance in financial statements so that it can affect Laras Puri Asih, I Gusti Agung Musa Budidarma changes in stock prices.…”
Section: Corporate Governance Mediation On Capital Structure and Shar...mentioning
confidence: 99%
“…Previous research conducted by (Karamoy & Tulung, 2020) found that corporate governance and financial performance have no effect on stock prices. According to (Pendong et al, 2022), good corporate governance can be interpreted as a structure and system that regulate the relationship between management (agents) and shareholders (principals). So there needs to be attention paid to company performance and the implementation of good corporate governance in financial statements so that it can affect Laras Puri Asih, I Gusti Agung Musa Budidarma changes in stock prices.…”
Section: Corporate Governance Mediation On Capital Structure and Shar...mentioning
confidence: 99%
“…Meanwhile, internal factors that can influence Non-Performing Financing (NPF) include the implementation of Good Corporate Governance (GCG). Good Corporate Governance (GCG) is like a set of rules and guidelines that help companies control a performance system (Rahayu & Kartika, 2022). Implementation of GCG ensures that the bank follows sharia principles in everything it does, which can help banks become better at what they do and become more successful, which will certainly make people trust sharia banks (Raharjanti & Muharrami, 2020).…”
Section: Introductionmentioning
confidence: 99%